Association between asthma and migraine: A cross‐sectional study of over 110 000 adolescents. (4th October 2018) - Graif, Yael; Shohat, Tamy; Machluf, Yossy; Farkash, Rivka; Chaiter, Yoram
Abstract: Background: Epidemiological studies have reported an association between asthma and migraine, mainly in adults. Objective: To examine the association between specialist‐diagnosed asthma and migraine among adolescents. Methods: The electronic database of a recruitment center was retrospectively searched for all 17‐year‐old draftees during the years 1987‐2010. Diagnoses of asthma and migraine were made by certified specialists. The prevalence of migraine was compared among draftees with and without asthma. Covariate data on socio‐demographics and associated medical conditions were recorded. Results: A total of 113 671 adolescents were available for analysis. Asthma was diagnosed among 4.0% and migraine among 1.9%. Migraine was significantly more prevalent among adolescents with asthma [174 of the 4581 subjects (3.8%)] compared to those without asthma [1946 of the 109 090 (1.8%)] [OR = 2.17 (95% CI 1.86‐2.55; P  < 0.001)]. Rates of migraine among subjects with and without allergic rhinitis were 6.3% and 1.7%, respectively [OR = 4.04 (95% CI 3.58‐4.56; P  < 0.001)]. On multivariate analysis, there was a significant association between migraine and both asthma [OR = 1.42 (95% CI 1.19‐1.68)] and allergic rhinitis [OR = 3.18 (95% CI 2.80‐3.63)]. Other factors significantly associated with migraine were female gender, urban area of residence, recent immigration to Israel, having three or fewer siblings, and abnormal body mass index. Conclusion: Clinicians should be aware that asthma and allergic rhinitis are potential risk factors for migraine in adolescents. A combined finding of these conditions and recurrent headache is highly suggestive of migraine and warrants a different diagnosis and treatment approach from sinusitis.